1986
DOI: 10.1007/bf01658133
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic changes secondary to radiation

Abstract: In order to be effective in the treatment of disease, especially neoplastic disease, radiation necessarily needs to be given in large doses. When treating tumors with high radiosensitivity in tissue of relatively low radiosensitivity, few complications of therapy occur. Frequently, however, the differential of sensitivity to radiation between the neoplasm and normal tissues exposed is small and the incidence of radiation injury to normal tissues becomes significant. Nowhere is this more apparent than in treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

1987
1987
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(41 citation statements)
references
References 50 publications
0
32
0
4
Order By: Relevance
“…[2][3][4] Bacterial translocation is defined as the passage of viable endogenous bacteria and endotoxins from the gastrointestinal tract to extraintestinal sites such as the mesenteric lymph node (mLN) complex, liver, spleen, kidney, and bloodstream. 5,6 Endotoxemia and bacteremia are critical events in the pathogenesis of GI-ARS, and the colon is the primary source of endotoxins, which thus highlights the importance of this tissue's injury during radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Bacterial translocation is defined as the passage of viable endogenous bacteria and endotoxins from the gastrointestinal tract to extraintestinal sites such as the mesenteric lymph node (mLN) complex, liver, spleen, kidney, and bloodstream. 5,6 Endotoxemia and bacteremia are critical events in the pathogenesis of GI-ARS, and the colon is the primary source of endotoxins, which thus highlights the importance of this tissue's injury during radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiation has a cytotoxic effect on the intestinal mucosa by increasing the levels of free oxygen radicals 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical analysis, in vitro and in vivo, animal and human studies along with phase I-phase II human clinical trials with pilot phase III clinical trials have shown that oral GLN is a safe and effective strategy to prevent and treat mucositis, stomatitis and cachexia [2][3][4][5][6]8,11,12,[15][16][17][18][20][21][22]25,26,[29][30][31][32][33][34]38,39 (M. M. Schubert, unpublished data, 2004). Concerns about GLN being preferentially used by the cancer cells, giving a tumorprotective effect, have been addressed in the research.…”
Section: Resultsmentioning
confidence: 99%
“…2 Normal tissue damage from radiation and or chemotherapy, especially in the GI tract, influences the presence of adequate GLN stores in the tissues and can also contribute to cachexia. 4,7,18 A by-product of GLN metabolism is GSH, which protects against oxidative injury. The gut is the major site of GSH production.…”
Section: Cancer Cachexia Prevention and Treatment With Glutaminementioning
confidence: 99%